2019
DOI: 10.1002/wcc.586
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating agricultural weather and climate services in Africa: Evidence, methods, and a learning agenda

Abstract: Weather and climate services (WCS) are expected to improve the capacity of Africa's agricultural sector to manage the risks of climate variability and change. Despite this, a lack of evidence prevents a realistic analysis of whether such services are delivering on their potential. This paper reviews 66 studies that have evaluated outcomes and/or impacts of agricultural WCS in Africa, highlighting areas that have received relatively more attention as well as persistent gaps. While the evaluation of WCS outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
87
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 71 publications
5
87
0
Order By: Relevance
“…A recent Africa-focused review of published evidence on CIS for farmers found considerable variability in rates of access, but in most cases (with exceptions that include women farmers in Mali, and pastoralists) the majority of farmers who access CIS use it in their decision-making [53]. It highlighted challenges to reliably estimate how the use of CIS translates into agricultural productivity and livelihood benefits.…”
Section: Climate Information Servicesmentioning
confidence: 99%
“…A recent Africa-focused review of published evidence on CIS for farmers found considerable variability in rates of access, but in most cases (with exceptions that include women farmers in Mali, and pastoralists) the majority of farmers who access CIS use it in their decision-making [53]. It highlighted challenges to reliably estimate how the use of CIS translates into agricultural productivity and livelihood benefits.…”
Section: Climate Information Servicesmentioning
confidence: 99%
“…Among climate smart approaches, the CIS remains a credible option for boosting productivity and avoiding postharvest losses (FAO, 2013). CIS is referred to as the production, translation, transfer, and use of scientific information for decision-making (Serra & McKune, 2016;Vaughan, Hansen, Roudier, Watkiss, & Carr, 2019). Recent studies by Ouedraogo, Diouf, Ou edraogo, Ndiaye, and Zougmor e (2018) revealed that access and use of climate information helped Senegalese farmers make tactical decisions before, during, and after the farming seasons.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies by Ouedraogo, Diouf, Ou edraogo, Ndiaye, and Zougmor e (2018) revealed that access and use of climate information helped Senegalese farmers make tactical decisions before, during, and after the farming seasons. Within SSA, several benefits of CIS in improving agricultural productivity and resource use efficiency are reported (Etwire et al, 2017;Dinesh, 2016;Roudier et al, 2014;Serra & McKune, 2016;Vaughan et al, 2019;Zougmor e & Ndiaye, 2015). However, the gender perspective concerning determinant of access to climate information services is poorly documented (Carr, Fleming, & Kalala, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant efforts supported by various organizations to promote availability, access and use of climate services, the economic value of existing or potential climate services is not well understood, particularly for smallholder farmers in Africa (e.g. Clements et al, 2013;WMO, 2015;Vaughan et al, 2018). Because climate services are provided often freely through the mass media as public goods in most countries, market value cannot be used to estimate their economic value (Gunasekera, 2010;Rollins and Shaykewich, 2003).…”
Section: Introductionmentioning
confidence: 99%